Maslahat and Mafsadat Discourse in Polygamy Practice: A Study Of The Implementation of Fiqh Rules - Nasrul Fatah; Hasbullah, Robi; Maghfirah; Muhammad Hafiz Saleh (West Science Interdisciplinary Studies, 2025)
Islamic law is essentially in accordance with basic human needs and is oriented towards achieving maslahat and preventing mudharat, henceforth known as the concept of dharuriyyat al khams and maqashid shari'ah. However, conditions where maslahat and mudharat exist simultaneously are not uncommon in life, for example in the case of polygamy. On the one hand, it has maslahat to avoid sin, but on the other hand, it has the potential to cause conflict and the end of household relationships. So this research aims to apply one fiqh rule Dar'ul Mafȃsid Muqaddam 'Alȃ Jalbil Mashȃlih. This research is a literature research with a qualitative approach. This study concludes that based on existing data, the practice of polygamy is better avoided in cases where there is no permission from the first wife to avoid the emergence of conflict.